Combined Precoding Tehcnique with Antenna Selection for Massive MU-MIMO Systems - Bakulin, M. G.; Ben Rejeb, Taoufik; Kreyndelin, V. B.; Smirnov, A. E. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
Frequency plan of the new standard of mobile communication systems 5G New Radio contain a large number of time division duplex bands. At the same time number of antennas in MIMO systems increases at the both sides on base station and on user equipment. The main goal of new technologies applying is to achieve high throughput according new enhanced mobile broadband scenarios: eMBB, uRLLC, mMTC. There are a lot of different methods for spatially signals processing, including precoding, beamforming, space-time codes, antenna selection. We proposed combined precoding technique with antenna selection, based on channel reciprocity principle, implemented in frequency bands with TDD mode. Proposed precoding technique with antenna selection can significantly increase the energy efficiency of multi-antenna systems with antenna configurations of the considered type, where user equipment has a large number of antennas. In addition, the proposed precoding algorithm has a low computational complexity and does not require the high efficiency feedback channel.